Keanekaragaman Jenis Echinodermata Di Zona Litoral Pantai Oesina Kecamatan Kupang Barat Kabupaten Kupang - Melianus Yufren Lopo; Aloysius Djalo; Florentina Yasinta Sepe (JBIOEDRA: Jurnal Pendidikan Biologi, 2023)
Diversity of Echinodermata Types in the Oesina Beach Littoral Zone, West Kupang District, Kupang Regency. This research aims to determine the types of Echinoderms in the Oesina Beach Littoral Zone, West Kupang District, Kupang Regency. This research was carried out at Oesina beach, Lifuleo village, West Kupang District, Kupang Regency on 5-10 May 2023 This research uses a quantitative descriptive approach using an exploration method, namely conducting direct observations of echinoderms on Oesina beach, Lifeleo Village, West Kupang District, Kupang District. The research results found that from 4 transects in 15 plots, various types of Echinodermata were found, namely 7 species consisting of 6 families, 6 classes, 4 orders, 6 genera and 2 sub-phyla with a total of 120 individuals. The phylum Echinodermata is the class of sea stars (Asteroidea), brittle stars (Ophiuroidea), sea cucumbers (Holothuroidea) and sea urchins (Echinoidea). Species found at the observation location include Archaster typicus, Ophiarachna affinis, Protoreaster nodulosus, Echinometra oblonga, Echinometra mathae, Holothuria leucospilota, Tripneustes gratilla. The results of calculating the diversity index (H) of echinoderms on Oesina beach, Lifeleo Village, West Kupang District, Kupaten District, are in the high category The conclusion is that the level of diversity of echinoderms in the Oesina Coastal Littoral Zone, West Kupang District, Kupang Regency is 1.83135 which shows high diversity.